Corrosion behavior of Al-3.0 wt%Mg alloy in NaCl solution under magnetic field - Zhang, Xin; Wang, Ze-Hua; Zhou, Ze-Hua; Xu, Jian-Ming; Zhong, Zhao-Jun; Yuan, Huan-Long (Rare metals, 2017)
The influences of applied magnetic field on the corrosion behavior of Al-3.0 wt%Mg alloy in 3.5 wt% NaCl solution were investigated by electrochemical measurements,scanning electron microscopy（SEM）and energy-dispersive spectroscopy（EDS）.Stochastic analysis was applied to investigate the influences of applied magnetic field.The results indicate that the application of horizontal magnetic field of 0.4 T would increase the pitting corrosion potential（E_（pit））,decrease the corrosion current density（i_（corr））,prolong the pit initiation time,slow down the pit generation rate and inhibit the growth of pitting of the tested alloys in 3.5 wt% NaCl solution.The applied magnetic field would also change the mechanism of pit initiation of Al-3.0 wt%Mg alloy from A_3 model（without magnetic field）to A_3＋A_4 model（with magnetic field）.The intermediate product Al_（（ad））~＋ is the paramagnetic ion that would be influenced by magnetic field sensitively.